Interaction of gravity waves with bottom-standing submerged structures having perforated outer-layer placed on a sloping bed. (August 2015) - Koley, S.; Sarkar, A.; Sahoo, T.
Abstract : Highlights: Wave interaction with bottom-standing breakwater placed on sloping bed is studied. The breakwater consists of inner rigid core and perforated outer layers. Sollitt and Cross model is used to study wave motion within the perforated layer. The problem is solved using eigenfunction expansion and boundary element methods. An effective wave trapping system can be developed using suitable parameters. Abstract: The present study deals with the interaction of oblique surface gravity waves by bottom-standing submerged structures having perforated outer-layers with the structure being placed on a sloping sea bed. Both the cases of wave scattering by a submerged structure and wave trapping by a submerged structure located near a wall are studied in water of finite depth under the assumption of small amplitude water wave theory. Sollitt and Cross model is used to analyze the wave motion within the perforated layer of the structure. The mathematical model of the physical problem is handled for solutions using a suitable combination of the eigenfunction expansion method and the boundary element method. Various aspects of structural configurations and wave characteristics on scattering and trapping of surface gravity waves are analyzed from the computed results on the reflection and transmission coefficients and the hydrodynamic forces acting on the structure and the rigid wall. It is observed that suitable configurations and location of the submerged structure can provide long-term and cost-effective solutions for creating a tranquility zone and in protecting various marine facilities from wave attack during extreme wave climate. Further, the outer perforated layer of the structure plays a significant role in reducing the wave forces on the submerged structure by dissipating a part of the wave energy, which in turn increases the service life of the structure as a wave barrier. The method does not require the solution of the complex dispersion relation and can be applied to analyze a large class of complex wave-structure interaction problems of practical interest in ocean engineering and other branches of mathematical physics.